PERSEPSI SISWA TERHADAP PEMBELAJARAN SEJARAH DI MAN LEMBAH GUMANTI KABUPATEN SOLOK - Yarni, Nofia Tika (Pendidikan Sejarah, 2014)
Teaching and learning of history subject at MAN Lembah Gumanti Kabupaten Solok stiil found several problem especially, learning objectivies, teaching material, media, method of teaching and evaluation. The purpose of this research to investigate students perception toward teaching of history at MAN Lembah Gumanti Kabupaten Solok. The kind of this research was descriptive qualitative analysis. The result of this research student perseption toward teaching of history for learning objectives, method, media and evaluation is not good. It can be proved in teaching history, teacher seldom explain the learning objectives so the student did not understand the meaning of learning objectives similiar to method, teacher often explain and it make the student felt bored. From the media used by the teacher, they often used text book and LKS only. It made the student borring. Teacher should creative in designing the learning media such as chart, map,etc. Another case teacher seldom evaluate the student comprehension such orall test or written test, they only did an daily test, mid term, and final test ang assignment. The assignment only collected and seldom to be discussed. The perception of student toward material of history categorized as good. Because the student under standabout it and the languange used by the teacher in explaining the material was good. So, it can be concluded that student perseption toward learning objectives, method, media and evaluation is not good, in contrast the perseption of student toward material of history is good.